Testing and application of wire mesh sensors in vertical gas liquid two-phase flow - Sharaf, Safa (2012)
The behaviour of gas-liquid two-phase flow has been studied extensively in the past at near atmospheric pressure in small diameter pipes. However, the industrial reality is the utilisation of large diameter pipes at elevated pressures and there is significantly less information available in this area due principally to the cost of investigating large diameter pipes. This research relied on using large-scale laboratory facilities at the University of Nottingham, and on using newly developed state of the art multiphase instrumentation. This study tested and applied the wire mesh sensor (WMS). The work included in this thesis utilised the two variants of the WMS; the already established Conductivity WMS and the recently developed Capacitance WMS and the two sensors were compared against each other. The Capacitance WMS was recently supplied by HZDR (Research Institution, Germany) to the University of Nottingham. Extensive experimental campaigns were carried out with this novel sensor. The WMS was initially tested and validated against several other instruments such as high speed camera and gamma densitometry. It was subsequently applied to a large diameter bubble column and large diameter pipe with two phase flow. The aims of this project was to gain a better understanding of the flow patterns and their transitions in large diameter pipes and to provide real experimental data to assist researchers and engineers in producing relevant and physically sound models for use in larger diameter pipes. As a result of this study, novel and interesting structures which have been labelled as wisps were discovered in large diameter pipes. In addition the WMS was used extensively for the first time on bubble columns in order to assess its suitability for such an application.